Edukasi Pertanian Berkelanjutan dalam Manajemen Produksi dan Pemasaran Pada Usaha Tani Nanas Pamboang, Kabupaten Majene - Arifan Adhy DJ; Ihsan Arham; Anis Anshari Mas’ud (MALLOMO: Journal of Community Service, 2025)
AbstractThis community service program aimed to enhance the knowledge and skills of pineapple farmers in Betteng Village, Pamboang District, Majene Regency in managing the local Pamboang pineapple cultivation through environmentally sound and economically empowering approaches. The activities consisted of surveys, socialization, training, and monitoring to strengthen farmers’ understanding of sustainable production management, organic waste handling, business planning, product diversification, and digital-based marketing. Training sessions combined technical demonstrations of compost production from pineapple plant residues with managerial guidance related to enterprise development and market expansion. Quantitative assessments showed a substantial increase in participant knowledge, rising from initial levels to significantly higher levels after the training, accompanied by strong positive perceptions of the program’s relevance and usefulness. Most participants reported direct benefits, improved motivation, and greater confidence to apply sustainable cultivation techniques and explore economic opportunities through processed pineapple products and digital promotion. The program concluded that capacity-building efforts grounded in participatory methods, practical demonstrations, and continuous evaluation can effectively support the sustainability of local pineapple agribusiness and contribute to long-term community welfare. AbsrtrakProgram pengabdian ini bertujuan meningkatkan pengetahuan dan keterampilan petani nanas varietas lokal Pamboang di Desa Betteng, Kecamatan Pamboang, Kabupaten Majene dalam mengelola usaha tani nanas pamboang secara berkelanjutan melalui pendekatan ramah lingkungan dan penguatan ekonomi. Kegiatan dilaksanakan melalui tahapan survei, sosialisasi, pelatihan, serta monitoring untuk memperdalam pemahaman peserta mengenai manajemen produksi berkelanjutan, pengelolaan limbah organik, perencanaan usaha, diversifikasi produk olahan, dan pemasaran berbasis digital. Pelatihan menggabungkan demonstrasi teknis pembuatan kompos dari residu tanaman nanas dengan materi manajerial tentang pengembangan usaha dan perluasan pasar. Penilaian kuantitatif menunjukkan peningkatan signifikan pada tingkat pengetahuan peserta, disertai persepsi positif terhadap manfaat dan ketepatan pelaksanaan kegiatan. Sebagian besar peserta merasakan manfaat langsung, meningkat motivasinya, serta percaya diri dalam menerapkan teknik budidaya berkelanjutan dan peluang usaha berbasis olahan nanas serta promosi digital. Program ini menyimpulkan bahwa peningkatan kapasitas melalui metode partisipatif, praktik langsung, dan evaluasi berkelanjutan efektif mendukung keberlanjutan usaha tani nanas pamboang dan kesejahteraan masyarakat dalam jangka panjang.